Effect of Incorporating TiO2 Photocatalyst in PVDF Hollow Fibre Membrane for Photo-Assisted Degradation of Methylene Blue - Norashima Abdullah; Bamidele Victor Ayodele; Wan Nurdiyana Wan Mansor; Sureena Abdullah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
A rapid growth in populations, living standards and industries has become a key contribution to water pollution. Clean water is an important resource for life, sustainable development and ecosystems. This study therefore investigates the photocatalytic degradation of an organic pollutant (methylene blue) using PVDF/TiO2 membrane. The main objective of the study is to determine the synergistic effect of incorporating TiO2 photocatalyst into the PVDF membrane on the mineralization of the organic pollutants. The TiO2 photocatalyst was characterized using Ultraviolet Visible Spectroscopy (UV-Vis), Scanning Electron Microscopy (SEM), Brunauer, Emmettt, and Teller (BET), and X-ray Diffraction (XRD) techniques. While the fabricated PVDF/TiO2 hollow fibre membranes were then characterized by scanning electron microscopy (SEM) and contact angle. The performance of the membrane was evaluated by photodegradation of methylene blue. The degradation study revealed that both the undoped PVDF and the TIO2 doped PVDF membrane were capable of degrading methylene blue. The performance of the membrane can be ranked as follows 9 wt% TiO2/PVDF > 6 wt% TiO2/PVDF > 3 wt% TiO2/PVDF > undoped PVDF showing the synergistic effect of incorporating the TiO2 photocatalyst into the PVDF membrane. The kinetics data of obtained from the rate of degradation of the methylene blue fitted well into first order kinetic data with apparent kinetic constants of 0.0591, 0.0295, 0.0188, and 0.0100 obtained using pure membrane, undoped PVDF, 3 wt% TiO2/PVDF, 6 wt% TiO2/PVDF, and 9 wt% TiO2/PVDF, respectively.